Performance of 'Valência' sweet orange grafted on trifoliate orange hybrid rootstocks - Domingues, Allan Ricardo (2022)
The objective of this work was to evaluate tree size, production, and fruit quality of 'Valência' sweet orange (Citrus sinensis) grafted on various trifoliate orange rootstocks, in order to select genotypes with a high performance. Twenty rootstock genotypes were evaluated, including trifoliate orange hybrids with mandarin (citrandarins) and with grapefruit (citrumelos), as well as 'Rangpur' lime. The experiment was implemented in the northwestern region of the state of Paraná, Brazil, in a 6.0×2.5 m spacing, in a sandy soil under subtropical and rainfed conditions. The statistical model used was the randomized complete block design with four replicates and four trees per plot. Tree size and fruit yield and quality were analyzed during three consecutive harvest seasons. Data were subjected to the analysis of variance, and means were grouped by the Scott-Knott test. Principal component analysis and agglomerative hierarchical clustering were also carried out. F.80-18, F.80-5, and F.80-3 citrumelos and IPEACS-239 citrandarin are adequate rootstock options for 'Valência' sweet orange, with dwarf trees and a high production efficiency. These rootstocks, except F.80-18, are also adequate options to obtain oranges with good industrial properties.